Evolution and Diversity of TGF-β Pathways are Linked with Novel Developmental and Behavioral Traits. (5th December 2022) - Lo, Wen-Sui; Roca, Marianne; Dardiry, Mohannad; Mackie, Marisa; Eberhardt, Gabi; Witte, Hanh; Hong, Ray; Sommer, Ralf J; Lightfoot, James W
Abstract: Transforming growth factor-β (TGF-β) signaling is essential for numerous biologic functions. It is a highly conserved pathway found in all metazoans including the nematode Caenorhabditis elegans, which has also been pivotal in identifying many components. Utilizing a comparative evolutionary approach, we explored TGF-β signaling in nine nematode species and revealed striking variability in TGF-β gene frequency across the lineage. Of the species analyzed, gene duplications in the DAF-7 pathway appear common with the greatest disparity observed in Pristionchus pacificus. Specifically, multiple paralogues of daf-3, daf-4 and daf-7 were detected. To investigate this additional diversity, we induced mutations in 22 TGF-β components and generated corresponding double, triple, and quadruple mutants revealing both conservation and diversification in function. Although the DBL-1 pathway regulating body morphology appears highly conserved, the DAF-7 pathway exhibits functional divergence, notably in some aspects of dauer formation. Furthermore, the formation of the phenotypically plastic mouth in P. pacificus is partially influenced through TGF-β with the strongest effect in Ppa-tag-68. This appears important for numerous processes in P. pacificus but has no known function in C. elegans. Finally, we observe behavioral differences in TGF-β mutants including in chemosensation and the establishment of the P. pacificus kin-recognition signal. Thus, TGF-β signaling in nematodes represents a stochastic genetic network capable of generating novel functions through the duplication and deletion of associated genes.